Design of calamitic self-assembling reactive mesogenic units: mesomorphic behaviour and rheological characterisation. Issue 4 (16th March 2018) - Bubnov, A.; Cigl, M.; Machado, A.; Pociecha, D.; Hamplova, V.; Cidade, M. T.
ABSTRACT: Several calamitic reactive mesogens containing only two benzene rings in the molecular core and with or without lateral substitution by the methyl/methoxy groups have been designed and their mesomorphic behaviour was characterised. Depending on the molecular structure, some of the materials exhibit the nematic and the orthogonal smectic mesophases. The reactive mesogens are aimed for further design of the macromolecular materials like polysiloxane-based polymers and elastomers. Beyond the mesomorphic and structural properties, the electrorheological properties within the temperature range of the nematic and smectic A mesophases were studied with and without applied electric field for the selected reactive mesogen. The increase of viscosity was found not to be higher than three times under applied electric field strength of 2 kV/mm. The mesomorphic, structural and rheological properties of the newly designed reactive mesogens are discussed in order to contribute to better understanding of the molecular architecture–nano-organisation properties relationship of such mesogenic materials. GRAPHICAL ABSTRACT: